PERAN BAHASA IBU TERHADAP KECERDASAN BAHASA TARGET ANAK USIA 4 - 5 TAHUN DI PAUD DARUSSALAMAH BARUH SAMPANG - Khoirul Anam (Pelangi Jurnal Pemikiran dan Penelitian Islam Anak Usia Dini, 2019)
This study is entitled The Role of Mother Language on Target Language Intelligence of Children 4-5 Years Old in Darussalam PAUD Baruh Sampang. With the aim of the study is to find out the role of mother tongue on the target language intelligence of children in using language and responding to effective words of communication, both verbally and in writing. The method used is a type of descriptive qualitative approach. Data collection techniques were used observation techniques, direct communication interview techniques and documentation study techniques. The scope and limitations of this study are children who study in Early Childhood Education (PAUD) Darussalamah in the village of Baruh, Sampang Regency. Data sources which are the main subjects of this study are; First, students who study in Darussalam PAUD. Second, the teachers as correctors and children’s language motivators. Third, parents are the children’s languageenvironment. The results of this research are those children who use Indonesian as the target languages in communication are adopted from the mother tongue first and the target language later. This is where the role of mother tongue as a corrector to correct children’s language errors in using the target language,especially the teachers and parents can help the language errors of children to improve their language correctly. In this study the authors assume that mother tongue can also contribute to children’s target language intelligence.